Fenomena Simplifikasi dan Desofistikasi Budaya Jawa di luar Jawa - A Anharudin; Misbah Zulfa Elizabeth (JSW (Jurnal Sosiologi Walisongo), 2019)
Culture will change with place and time. As a culture, Javanese culture has a tight characteristic. It is interesting to observe the culture among the Javanese community in Lampung which showed the desophistication in Javanese culture that they applied on. The term of “desophistication” in this context meant the loss of the sophisticated traits of Javanese culture or the lost original traits of Javanese culture as in Java mainland. The study was done by applying qualitative research, and the data were combined by involving intensively in the daily life of Javanese people within Javanese communities in Lampung, mainly those who had moved to these areas through the processes of colonization and transmigration, and their inheritances. This study uses an assumption that Javanese culture in the mainland of Java is very sophisticated, with the characteristics of "mystical", "mythological", "spiritualistic," and "ethical-aesthetic". Where as in the villages of Java's colonies and transmigrations in Lampung, have now undergone changes toward a simpler performance. The question that will be cover in this research area, what are the causes and determinant factors of such changes.